1968
DOI: 10.1139/p68-456
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the magnetic and phonon excitations in cobalt fluoride

Abstract: The excitations of cobalt fluoride have been studied with the technique of slow-neutron inelastic scattering. A triple-axis crystal spectrometer was used throughout in its constant Q mode of operation. Several of the branches of the phonon spectra were measured and are in reasonable agreement with calculations based on a very simple rigid ion model. The magnetic excitations are of interest because the Co2+ ion has unpaired orbital angular momentum which gives rise to several low-lying energy levels. Excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…We could not use the related published data for CoF 2 based on inelastic neutron scattering studies 21 and Mandelshtam-Brillouin scattering 5 because of the large (by more than a factor of 2) difference between them. Thus, we have provided the results of our own acoustic measurements of the elastic moduli using the "nonius" method 22 at frequencies of $54 MHz at liquid nitrogen temperature.…”
Section: The Elastic Moduli Of Cofmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not use the related published data for CoF 2 based on inelastic neutron scattering studies 21 and Mandelshtam-Brillouin scattering 5 because of the large (by more than a factor of 2) difference between them. Thus, we have provided the results of our own acoustic measurements of the elastic moduli using the "nonius" method 22 at frequencies of $54 MHz at liquid nitrogen temperature.…”
Section: The Elastic Moduli Of Cofmentioning
confidence: 99%
“…It seems that an error was made in some coefficient in the course of analyzing the experimental data of Ref. 21.…”
Section: The Elastic Moduli Of Cofmentioning
confidence: 99%
“…The magnetic excitations in CoF 2 were first studied by Lines [7] and the dominant exchange and anisotropy parameters were estimated by comparing theory with low-temperature antiferromagnetic resonance frequencies [8] and infrared absorption data [9]. The electronic stucture of the Co 2+ ions has been determined by Gladney [10], and the spin-wave dispersion relations have been measured by Cowley et al [11,12] using inelastic neutron scattering. Raman light scattering measurements made by Macfarlane [13], Moch et al [14], and Hoff et al [15] have also characterized the low-lying zone center excitations, and the light scattering cross sections [13,14] are somewhat consistent with the calculations of Ishikawa and Moriya [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lines found this approach to be satisfactory up to gTN. Following this method, and thus including contributions from just the lowest branch of the magnon energies for which Martel et al (1968)t have found values of the parameters which satisfactorily reproduce neutron scattering measurements, we are able to find a density of states and hence evaluate the specific heat contribution. I n fact we have used the six-line-integral interpolation formula of equation (6).…”
Section: Calculation Of the Spin-wave Contributions To The Specific Hmentioning
confidence: 94%